Redesain Environmental Graphic Taman Bungkul Surabaya dengan Teknik Vektor sebagai Upaya Optimalisasi Media Informasi - Mukadar, Winda Tri Astami; Bahruddin, Muh; Yosep, Sigit Prayitno (Jurnal Art Nouveau, 2016)
Taman Bungkul of Surabaya is one of the city parks that have a very important role for the development of Surabaya city as evidenced with being visited by their local travelers even foreign tourists. To make tourists understand more about the available facilities, it required a precise information media. The Information Media being said is containing the form of environmental graphic design such as sign system and wayfinding inside the park. In this scheme, the data has been obtained and analyzed by using multiple stages, namely data reduction stage, data presentation, and conclusion. After analyzing the data, we've discovered a design concept or a keyword which is "Satisfied". "Satisfied" means content or feeling happy (relieved, excited) because it fulfilled the desire of the heart. The concept of "Satisfied" aims to show that the results of the environmental graphic redesign, which is in Taman Bungkul of Surabaya, can facilitate visitors both local and foreign tourists, so they can understand the whole information that being presented. That is to say, the concept of "Satisfied" is expected for visitors whom have difficulty in activities within the park such as finding a way to understand the signs, wayfinding, as well as supporting media such as mini-map and wayfinding map, and visitors can feel satisfied with the information that being provided. Utilization of the vector technique aims for a design that can be easily understood by visitors. Keywords: Taman Bungkul, Environmental Graphic Design, Sign, Wayfinding, Satisfied, Vector.